The Emergence of Evidence Based Management: The Theoretical Perspective - Amin, Khalid (2007)
This dissertation discusses the notion of evidence based management from theoretical perspective. It throws light on the nature of ÃÂevidence in evidence based practices from epistemological and ontological viewpoint. There is a discussion on the motives of new management ideas in the context of evidence based management. It also critically evaluates the work on evidence based management by its proponents. The critical evaluation is supported by arguments of its critics and the author's own assessment of the idea.